Boron–nitrogen doped carbon scaffolding: organic chemistry, self-assembly and materials applications of borazine and its derivatives. Issue 83 (28th September 2015) - Bonifazi, Davide; Fasano, Francesco; Lorenzo-Garcia, M. Mercedes; Marinelli, Davide; Oubaha, Hamid; Tasseroul, Jonathan
Abstract : In this feature article we describe the past and recent developments in the organic synthesis and functionalisation of borazine, the isostructural inorganic analogue of benzene. Abstract : Discovered by Stock and Pohland in 1926, borazine is the isoelectronic and isostructural inorganic analogue of benzene, where the CC bonds are substituted by B–N bonds. The strong polarity of such heteroatomic bonds widens the HOMO–LUMO gap of the molecule, imparting strong UV-emitting/absorption and electrical insulating properties. These properties make borazine and its derivatives valuable molecular scaffolds to be inserted as doping units in graphitic-based carbon materials to tailor their optoelectronic characteristics, and specifically their semiconducting properties. By guiding the reader through the most significant examples in the field, in this feature paper we describe the past and recent developments in the organic synthesis and functionalisation of borazine and its derivatives. These boosted the production of a large variety of tailored derivatives, broadening their use in optoelectronics, H2 storage and supramolecular functional architectures, to name a few.